Perancangan Aplikasi Pencatatan Data Manifes Penumpang Kapal Penyeberangan Danau Toba Menggunakan Web - Tantri Hidayati Sinaga (STMIK Budi Darma, 2020)
Lake Toba Tourism Area, has the potential for natural tourism which is formed from super volcanic activities so that it makes it one of the favorite tourist attractions in Indonesia. The crossing ship is the main transportation in the Lake Toba tourism area and is a favorite choice for people around Lake Toba and tourists who want to visit Samosir Island. Passenger Manifest Data is a very important document in the process of transportation, especially airplanes and ships, including crossing ships on Lake Toba. The manifest contains data on passengers, crew members and various items transported by the mode of transportation. Manifest documents are also useful for the process of disbursing insurance for transportation accidents. Passenger Manifest data using crossing ships on Lake Toba currently only records the number of passengers and the number of vehicles riding the ship, but does not record the name of the passenger. Passenger manifest data application is needed to manage the manifest data of crossing ship passengers on Lake Toba, with the aim of facilitating monitoring of crossing activities and the process of identifying passenger crossing vessels. This research will produce an application to recording Passenger Manifest of crossing ship in Lake Toba. The application is based on web, so it will be easily accessed anywhere, and can only be accessed by the North Sumatra Transportation Office. This application can be used to make it easier for the parties involved in supervising and controlling the list of ship passengers who travel on Lake Toba, so that it can reduce the risk of accidents and misuse of the number of boat loads from the permit.